Pancasila sebagai paradigma pembangunan industri 4.0 - Hanum, Fathikah Fauziah (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
This article aims to find out the concept of Pancasila in the industrial revolution 4.0 by examining Pancasila as a development paradigm. The development includes economic, education and science and technology development. The Industrial Revolution is to become a vision in various lives, especially focusing on economic growth. The government is focused on improving the economy, education is also designed to be able to make human resources that can be competitive in the industrial sector. The problem is that the orientation of development which is more focused on facing industrial development causes the goal of forming the national personality to be reduced. This was followed by a weakening of national character. The development will not be great if it is not based on values manifested in the morality of the nation, so that reorientation of development is needed which refers to the Pancasila State philosophy, because Pancasila is basically a paradigm in development. The role of Pancasila is to provide some ethical principles to economic development, education and science, and technology.